EFEKTIVITAS PELAKSANAAN FUNGSI PENGAWASAN DI INSPEKTORAT DAERAH KABUPATEN KERINCI - Livia Simon Putra; Susi Susanti (Al Dzahab: Journal of Economics, Management, Business and Accounting, 2021)
Purpose: Rulers or leaders need to carry out supervision, because without supervision will result in deviations. The implementation of supervision, both seen from inspection, testing to investigation, has not been running effectively, this is due to the lack of timeliness in conducting supervision, the inaccurate data on deviations found for the supervisory apparatus at the District Inspectorate office. Kerinci. Basically, supervision is not intended to find fault and impose sanctions or penalties, but supervision is intended to find out the real reality regarding the implementation of organizational activities. Design/Methodology/Approach: This research was conducted with a qualitative approach. Data obtained directly from the object of research with data collection techniques, namely the interview method. Findings: The implementation of supervision has not been effective, this is due to the inaccuracy of time in conducting supervision, the inaccuracy of the deviation data found for the supervisory apparatus. Factors influencing the implementation of the Inspectorate's supervision in Kerinci Regency include officers who do not yet have good skills, the data used are not objective and unrealistic, and the lack of knowledge in the field of work being handled, even though the available facilities and infrastructure have supported the implementation of supervision. Research implications: Based on the research results that have been achieved, it is known that the implementation of supervision has not been fully effective, therefore the findings from this research become an input for the Kerinci Regency Inspectorate to improve the ability of employees in order to optimize reporting time.